A Compelling Formula Indicating the Existence of Ultra-low Energy Levels in the Hydrogen Atom (Global Journal of Science Frontier Research, 2022)
Abstract not found
Keywords: einstein’s energy-momentum relationship; ultra-low energy levels in the hydrogen atom